El uso de drones en seguridad y defensa: impactos y retos para el cumplimiento del DIH y la protección de los derechos humanos - Vargas Cano, Camilo Alberto; Gil-Osorio, Juan Fernando; Jimenez-Reina, Jonnathan (Estudios en Seguridad y Defensa, 2025)
The article explores the impact and challenges of the use of drones in security and defense, focusing on compliance with International Humanitarian Law and the protection of Human Rights. It describes the technological advances of the 20th and 21st century, highlighting how connectivity and modern technology have transformed armed conflicts. Through the case studies of Syria and Ukraine, the operational advantages of drone use are examined. However, it also addresses critical challenges, including lack of accountability, dehumanization of targets, and potential normalization of IHL and HR violations. The article concludes with the need for improved transparency, accountability and ethical training of drone operators to ensure respect for international humanitarian norms.